Cover. Issue 9 (1st September 2022) - Karlsson, Victoria; Sporre, Bengt; Fredén, Filip; Ågren, Johan
Abstract : The cover image is based on the Research Article Randomized controlled trial of low vs high oxygen during neonatal anesthesia: Oxygenation, feasibility, and oxidative stress by Victoria Karlsson et al., https://doi.org/10.1111/pan.14519 .